PNEUMOCOCCAL INFECTION IN HUNGARY - Z. Meszner (Union of pediatricians of Russia, 2014)
Editorial note. Dear colleagues! We continue introducing opinions of the leading foreign specialists in the sphere of specific immunoprophylaxis on the issues of pneumococcal infection and vaccination. In this issue we present to you an interview with Zsofia Meszner - MD, Professor of children's infectious diseases and pediatrics at the Faculty of Medicine of the Budapest University.